Printing green: microalgae-based materials for 3D printing with light [data] - Vázquez-Martel, Clara; Flórido Martins, Lilliana; Genthner, Elisa; Almeida, Carlos; Martel Quintana, Antera; Bastmeyer, Martin; Gómez Pinchetti, Juan Luis; Blasco, Eva (Universität, 2024)
Microalgae have emerged as sustainable feedstocks due to their ability to fix CO2 during cultivation, rapid growth rates, and capability to produce a wide variety of metabolites. Several microalgae accumulate lipids in high concentrations, especially triglycerides, along with lipid-soluble, photoactive pigments such as chlorophylls and derivatives. Microalgae-derived triglycerides contain longer fatty acid chains with more double bonds on average than vegetable oils, allowing a higher degree of post-functionalization. Consequently, they are especially suitable as precursors for materials that can be used in 3D printing with light. Herein, we present the use of microalgae as “biofactories” to generate materials that can be further 3D printed in high resolution In this study two taxonomically different strains —Odontella aurita (BEA 0921B) and Tetraselmis striata (BEA 1102B)— are identified as suitable microalgae for our purpose. The extracts obtained from the microalgae (mainly triglycerides with chlorophyll derivatives) have been functionalized with photopolymerizable groups and used directly as printable materials (inks) without the need for additional photoinitiators. The fabrication of complex 3D microstructures with sub-micron resolution is demonstrated. Notably, the 3D printed materials show biocompatibility. Our findings open new possibilities for the next generation of sustainable, biobased, and biocompatible materials with great potential in life science applications.
Gefördert durch: Deutsche Forschungsgemeinschaft (DFG, German Research Foundation) via the Excellence Cluster “3D Matter Made to Order”: EXC-2082/1-390761711; Carl Zeiss Foundation: Carl-Zeiss-Foundation-FocusHEiKA; Fonds der Chemischen Industrie: Kekulé Fellowship; European Territorial Cooperation Program PCT-MAC 2014-202: REBECA-CCT (MAC2/1.1.B/269)
Gesehen am 24.06.2024
Keywords: Forschungsdaten; Datenbank